Cystourethroscopy in the cat: What do you need? When do you need it? How do you do it?. Issue 1 (January 2014) - Berent, Allyson
Practical relevance: Diagnostic and therapeutic cystourethroscopy has become very popular in the diagnosis and treatment of canine lower and upper urinary tract disease in the past 5–7 years. As expertise is expanding, the use of similar techniques in feline patients is growing. Outline: This is a brief overview of the indications, equipment needed and procedure for performing cystourethroscopy in feline patients. The principal focus is normal feline lower urinary tract anatomy. Some examples of abnormalities that might be seen are also provided, and therapeutic cystourethroscopy is touched upon.